FACTORS TO FLIP CLASSES - Nazarova, L. (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
Flipped Classroom Model (FCM) has already become mostly pressed issue lately as it is undoubtedly helpful way to manage the classroom and students` learning. However, flipping the classroom may not be appropriate for every course or every instructor. There may be a time when other active learning strategies are more appropriate to meet learning outcomes, students’ needs, and instructor capacity. This paper discusses some factors that an instructor might consider before flipping their classroom which might also enhance their implementation of this and other teaching strategies.